Organization of equity accounting process technology - Slesar, Tеtiana; Shara, Yevheniia (Herald of Economics, 2021)
Introduction. The lack of a clear organization of equity accounting in enterprises with foreign investment causes problems in the formation of accounting and analytical support for management decisions not only by management but also by foreign investors, which reduces the inflow of investment into the company and the exit of investors.The purpose of the study is to clarify the content of the organization of accounting of equity in enterprises with foreign investment and study the specifics of the organization of the technology of the accounting process of equity at the stages of primary, current and final accounting.Research methods. In the process of research on the organization of the accounting process of equity were used general and special methods of cognition. General scientific methods - system approach, induction and deduction, analysis, synthesis and generalization - are used in processing information to clarify the content of the organization of accounting for equity in enterprises with foreign investment. Special methods of cognition are used to study the specifics of the organization of the technology of the accounting process of equity at the stages of primary, current and final accounting.Results of the research. According to the results of the analysis of literature sources, the content of the organization of accounting of own capital at the enterprises with foreign investments is specified.The provisions of the organization of accounting by clarifying the content of the stages of organization of accounting technology for equity in enterprises with foreign investment: primary, current and final accounting, as well as by specifying the lists of accounting information on equity (primary documents, accounting records, financial statements) , which are used in the accounting practice of enterprises with foreign investment, which necessitated the study of improving the documentation of records in accounting for equity transactions of enterprises with foreign investment.The organization of accounting of own capital at the enterprises with foreign investments on the basis of substantiation of influence of provisions of contract, constituent documents and accounting policy on the order of the organization of document circulation and formation of organizational nomenclatures of accounting is improved.The need for the formation of accounting nomenclatures for the organization of the accounting process as a whole, and the need to determine the accounting policy form of accounting and the procedure for registration of accounting information on equity in the registers of analytical and synthetic accounting.The list of provisions of the contract agreement which is defined proceeding from needs of its participants is resulted, and the aspects of legal maintenance of joint activity at drawing up of the contract agreement are defined.Perspectives. These results create prospects for the adaptation of modern enterprises with foreign investment to the needs of international capital markets, and with the help of specific organizational accounting regulations - accounting policy, which covers a set of principles, methods and procedures - the rules of equity accounting.